2012
DOI: 10.4161/cbt.18921
|View full text |Cite
|
Sign up to set email alerts
|

Selective tumor killing based on specific DNA-damage response deficiencies

Abstract: Overview of DNA-Damage Responses and SignalingThe genome of living organisms is constantly under the attack of exogenous and endogenous agents that damage their DNA potentially leading to harmful events such as single-or double-strand DNA breaks (SSBs or DSBs). 1 It is imperative for the organisms to resolve such damage and protect their DNA to maintain genomic stability, allowing for proper replication and proliferation. To counteract the deleterious effects of DNA-damaging agents, organisms have developed DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…The decrease of DNA damage over time may indirectly indicate DNA repair. Defective DDR has been reported to frequently occur in human cancers, making the DNA damage effect hypersensitive to cancer cells but insensitive to normal cells …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease of DNA damage over time may indirectly indicate DNA repair. Defective DDR has been reported to frequently occur in human cancers, making the DNA damage effect hypersensitive to cancer cells but insensitive to normal cells …”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the 8-oxodG type of oxidative DNA damage was higher in 4bHWE-treated oral cancer cells than that of HGF-1 cells using Fpg-comet ( Figure 6) and 8-oxodG-based flow cytometry (Figure 7) analyses. reported to frequently occur in human cancers, 43 making the DNA damage effect hypersensitive to cancer cells but insensitive to normal cells. 43 Consistently, we found that the gH2AX foci formation of 4bHWE-…”
Section: Bhwe Selectively Activates Oxidative Dna Damagementioning
confidence: 99%
See 1 more Smart Citation
“…ATM is most closely associated with the double-stranded DDR through checkpoint kinase 2 (Chk2), ATR is associated with the single-stranded DDR though checkpoint kinase 1, and DNA-PK is associated with the repair of double-stranded breaks through non-homologous end-joining (NHEJ) (Karran, 2000; Turnell and Grand, 2012). Once active, these apical kinases activate distal kinases, scaffolding proteins such as H2AX, and effector proteins such as p53 that direct DNA repair (Khanna and Jackson, 2001), cell cycle arrest (Zhou and Elledge, 2000), or cell death (Biss and Xiao, 2012). Adenovirus inhibits multiple steps of the DDR pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The key impediment to exploiting synthetic lethality in cancer therapy is the identification of robust synthetic lethal genetic interactions [ 6 ]. What makes DNA repair genes attractive targets for cancer therapy using the synthetic lethality approach is; (1) many DNA repair genes have synthetic lethal relationships with oncogenes and tumor suppressor genes, (2) many repair genes and repair pathways are upregulated in tumors giving rise to a distinct genetic profile that can be exploited for targeted killing of cancer cells, (3) several cancer cells are dependent on DNA repair pathways for survival in response to genotoxin stress (e.g., radio/chemotherapy) [ 6 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. In fact, in recent years, the success of poly(ADP ribose) polymerase inhibitors (PARPi): small molecules that inhibit the molecular and cellular function of PARP-1 and in doing so exploits the synthetic lethal relationship between PARP and BRCA1 or BRCA2 in BRCA1/2-null (ovarian or breast) tumors in response to platinum-based chemotherapy has made chemically induced synthetic lethality more mainstream in the development of new generation anti-cancer drugs [ 25 , 26 ].…”
Section: Leveraging Insights From the Biology Of Rare Genetic Disementioning
confidence: 99%